N–2 repetition leads to a cost within working memory and a benefit outside it. Issue 1 (15th March 2018) - Kessler, Yoav
Abstract: Removal has been suggested to play a key role in controlling the contents of working memory. The present study examined the aftereffects of removal in a working memory updating task. Participants performed the reference‐back paradigm, a version of the n‐back task that is composed of two trial types: reference trials that required working memory updating and comparison trials that did not require updating. N –2 repetition effects—the difference in performance between trials that presented the same stimulus as the one presented two trials before (ABA sequences) and trials in which the stimulus differed from the two previous stimuli (ABC sequences)—were examined. In two experiments, n –2 repetition costs were observed within sequences of reference trials, while n –2 repetition benefits were observed within sequences of comparison trials. This pattern suggests that removal takes place during working memory updating. Furthermore, automatic formation and updating of representation outside working memory, which takes place in comparison trials and gives rise to n –2 repetition benefits, does not involve removal. Removal, demonstrated by phenomena such as n –2 repetition costs, is therefore proposed to be a marker for the utilization of working memory within a given task.